Nursing of a patient with malignant peritoneal mesothelioma (1例恶性腹膜间皮瘤患者的护理体会) - WAN Zhengzheng (万铮铮); JIA Xuefei (贾雪飞); REM Jie (任洁) (中西医结合护理)
To summarize the nursing of a patient with malignant peritoneal mesothelioma. The key points of nursing include: pain control and nursing, nutrition risk screening and nutrition support, nursing and management of falls and insomnia, maintenance of infusion port, and psychological care. Targeted nursing interventions are effective to relive the pain and other symptoms and improve the patient adherence to the treatment (本文总结1例恶性腹膜间皮瘤患者的护理经验。护理要点包括: 疼痛的护理和处理, 营养风险筛查及营养支持, 跌倒、失眠的护理, 输液港的维护, 心理护理。通过开展针对性治疗和护理, 有助于缓解患者不适症状, 提高治疗依从性。)